PENGARUH PENAMBAHAN BUBUK KAYU MANIS (Cinnamomum burmannii) TERHADAP SIFAT KIMIA DAN TOTAL MIKROBA PADA NUGGET AYAM - Anto Anto; Rahman Rato (Agropolitan, 2018)
This study was conducted to determine the effect of adding cinnamon (Cinnamomum burmanni) powder to the chemical and microbial activity of chicken nuggets. The research method used completely randomized design (RAL) with four treatment 3 replication. The result of organoleptic test showed chicken nuggets with the addition of 2.5 g cinnamon powder most preferred. Chemical test showed that chicken nugget with the addition of cinnamon powder 2.5 g of moisture content of 69.51%, ash content of 1.15% and 13.22% protein content. The result of the microbial (TPC) test showed that at 0 day storage of chicken nugget without cinnamon were 44 cfu/g into 36 cfu/g. The addition of 2.5 g cinnamon powder, at 5 days about 80 cfu/g into 71 cfu /g, at 10 day ie 93 cfu / g into 82 cfu/g, at 15 days about 115 cfu/g into 96 cfu/g.